Facial emotion recognition, socio-occupational functioning and expressed emotions in schizophrenia versus bipolar disorder. (June 2018) - Thonse, Umesh; Behere, Rishikesh V.; Praharaj, Samir Kumar; Sharma, Podila Sathya Venkata Narasimha
Highlights: This is one of the first study to examine associations between Facial Emotion Recognition and Expressed Emotions experienced from care givers in two groups of major mental disorders Schizophreniaand Bipolar Disorder in remission. An important observation from our study is the presence of significant expressed emotions from care givers and facial emotion recognition deficits in patients with Bipolar Disorder in remission and its association with poorer adaptive living skills. Abstract: Facial emotion recognition deficits have been consistently demonstrated in patients with severe mental disorders. Expressed emotion is found to be an important predictor of relapse. However, the relationship between facial emotion recognition abilities and expressed emotions and its influence on socio-occupational functioning in schizophrenia versus bipolar disorder has not been studied. In this study we examined 91 patients with schizophrenia and 71 with bipolar disorder for psychopathology, socio occupational functioning and emotion recognition abilities. Primary caregivers of 62 patients with schizophrenia and 49 with bipolar disorder were assessed on Family Attitude Questionnaire to assess their expressed emotions. Patients of schizophrenia and bipolar disorder performed similarly on the emotion recognition task. Patients with schizophrenia group experienced higher critical comments and had a poorer socio-occupational functioning as compared to patients with bipolar disorder. Poorer socio-occupational functioning in patients with schizophrenia was significantly associated with greater dissatisfaction in their caregivers. In patients with bipolar disorder, poorer emotion recognition scores significantly correlated with poorer adaptive living skills and greater hostility and dissatisfaction in their caregivers. The findings of our study suggest that emotion recognition abilities in patients with bipolar disorder are associated with negative expressed emotions leading to problems in adaptive living skills.